Exploring the .NET Core 3.0 runtime : through code generation and metadata inspection - Villela, Roger (Apress, 2019)
"Explore advanced .NET APIs and create a basic .NET core library with dynamic code generation and metadata inspection to be used by other libraries or client applications. This book starts with the benefits of .NET including its fundamental tasks and tools where you will learn .NET SDK tools and the ILDasm tool. This is followed by a detailed discussion on code generation in .NET API programming. Along the way, you will learn how to build a programming model through a code-generator tool and metadata inspector tool using .NET version information for .NET assembly and binary code. Exploring the .NET Core 3.0 Runtime covers the features of Microsoft Visual Studio 2019 using a tutorial and shows you how to create a .NET Core 3.0 application. Here you will configure and deploy your .NET projects along with meta packages and see some do's and don'ts. Finally, you will compare the features of .NET Core 3.0 with the .NET Framework library and its GUI frameworks. After reading this book, you will be able to work in a .NET 3.0 environment and program for its two advanced features: code generation and metadata inspection. What You Will Learn Understand the inner workings of an assembly's structural organization Work with reflection through the .NET Core platform Carry out dynamic code generation using the .NET Core API's code document model (CodeDOM) Use the metadata mechanism of the .NET Core platform Who This Book Is For Software developers and engineers using .NET and/or the .NET Core platform and tools."